MARKET MECHANISMS IN UKRAINE FOR ESTABLISHING LAND OWNERSHIP AND USE - Batura , М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Market mechanisms play a key role in shaping land ownership and land use. After Ukraine became independent, the country faced the need to reform land relations, which in turn led to the creation of a complex system that regulates these relations. Ukraine is an agrarian state that has great potential in agriculture, therefore the formation of land ownership and land use is one of the key components of the agrarian policy of the state. The land reform, which began in the 1990s, aimed to transform the management of land resources from a collective form (Soviet) to a market one, that is, the development of market mechanisms, private property and efficient land use. In general, land ownership is the right to own a plot of land, which means the right to own a plot of land by a person or organization and have the right to dispose of it, whether it is to sell, bequeath or lease it, and land use is the right to use a plot of land, independently of whether the person or organization is the owner of the land plot. The land market is a crucial part of any country's economy. In Ukraine, the agricultural sector plays a vital role in driving economic growth and contributing to GDP. Therefore, establishing effective market mechanisms to regulate and allocate the country's land resources is of utmost importance. In 2021, Ukraine made significant progress by opening its land market; however, challenges arose regarding legislative regulation, transparency, and the efficiency of market mechanisms. This led to a need for improvements to ensure fair participation for all market players, including small farmers and large agricultural holdings. The long-term development of these market mechanisms holds great potential. It is expected to strengthen the country's economy, enhance efficiency in agriculture, and, importantly, improve living conditions in rural areas.